3D polycrystalline discrete element method (3PDEM) for simulation of crack initiation and propagation in granular rock. (October 2017) - Li, X.F.; Li, H.B.; Zhao, J.
Abstract: A three-dimensional Voronoi tessellation model based on the distinct element method (DEM) is proposed to model the representative part of the microstructures of granular brittle rocks. Regularization is employed to decrease the frequency of polyhedrons with large edge ratio and contributes to a higher efficiency for element meshing. Sensitivity analyses are performed for a series of micro contact parameters in accordance with the macro responses observed in laboratory experiments (e.g. the uniaxial compression test, the Brazilian disc test and the triaxial compression test). Verifications by simulating the spalling test and plate impact test indicate that the 3D polycrystalline discrete element method (3PDEM) can be employed for efficiently simulating nonlinear mechanical behaviors, large deformation, strain softening and rock dynamics.